PENGARUH PROFITABILITAS, LEVERAGE DAN UKURAN PERUSAHAAN TERHADAP PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY PADA PERUSAHAAN SEKTOR PERTAMBANGAN YANG TERCATAT DI BEI TAHUN 2013-2017 - Shelly Indriastuty; Abel Tasman (Universitas Negeri Padang, 2019)
The purpose of this research are to analyze: (1) The effect of profitability on corporate social responsibility (2) The effect of leverage on corporate social responsibility (3) The effect of size on on corporate social responsibility. The population on this research is mining companies listed on BEI for the period 2013-2017. Based on purposive sampling, there are 165 companies’ years. This study uses multiple linier regression analysis techniques. The result of this research shows that (1) Profitability has a positive and not significant effect on corporate social responsibility (2) Leverage has a negative and significant effect on corporate social responsibility (3) Size has a positive and significant effect on corporate social responsibility. This research suggestion is (1) Management is expected to be able to understand and analyze corporate social responsibility and its impact on the company (2) The owner of the company is expected to be able to coordinate the management of the company to understand business ethics (3) For further researcher it is recessary to increase population and more representative samples. Keyword: corporate social responsibility, profitability, leverage and size